Linking through-thickness cracks in metallic thin films to in-situ electrical resistance peak broadening. (15th April 2022) - Gebhart, David D.; Krapf, Anna; Gammer, Christoph; Merle, Benoit; Cordill, Megan J.
Graphical abstract: Abstract: Measurements of electrical resistance have been used extensively as a failure criterion in cyclically loaded conductive films. However, not much research has been performed on extracting additional information contained within such resistance data sets. This study shows that an increase in peak width evidences a transition from cracks bridging to through-thickness crack formation. A Au/Cr bilayer system on a polyimide substrate is used for data generation but the method is applicable to any material system where both necking and through-thickness cracks are formed and no immediate formation of electrically insulating oxide layers occurs upon damage initiation. The method is easy to implement, and has the ability to replace time-intensive and destructive inspection methods.